Tantangan dan Strategi Pengamanan di Lembaga Pemasyarakatan Kelas IIA Lombok Barat - Jagad, Suluhuddin Puji (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
This study aims to analyze the effectiveness of the security system at Class IIA West Lombok Correctional Facility, which faces multidimensional challenges. The research employed a qualitative method with a case study design. Data were collected through in-depth interviews with 15 informants (officers and inmates), participatory observation for 30 days, and documentation studies. The results revealed three key themes: (1) Severe infrastructure and human resource limitations, marked by 250% overcapacity and an officer-to-inmate ratio of 1:30, were the root cause of tension and hindered effective supervision; (2) The implementation of Dynamic Security, colored by the local wisdom of